Pathological changes in the tiger prawn, Penaeus monodon Fabricius, associated with culture in brackishwater ponds developed from potentially acid sulphate soils - Nash, G.; Anderson, I. G.; Shariff, Mohamed (John Wiley & Sons, 1988)
Abnormal brown discoloration of the gills, soft shells and decreased survival were identified among problems affecting Penaeus monodon Fabricius adults cultured in growout ponds developed from potentially acid sulphate mangrove soils in Johor, Malaysia. A histological and ultrastructural study showed that lamellar ferric hydroxide accumulation and associated gill changes, which led to hypoxic damage in other tissues, were probably responsible for many of the clinical abnormalities observed in the prawns.